Langmuir Probe Measurements in a Dual-Frequency Capacitively Coupled rf Discharge - Schleitzer, Jessica; Schneider, Viktor; Korolov, I.; Hubner, G.; Hartmann, P.; Schulze, J.; Kersten, Holger (IEEE transactions on plasma science, 2024)
A dual-frequency ( 2f ) capacitively coupled rf argon plasma has been investigated using a passively compensated Langmuir probe (LP). The discharge is driven by two different excitation frequencies (13.56 and 27.12 MHz) simultaneously with a variable phase angle θ between them, utilizing the electrical asymmetry effect (EAE). Two plasma chambers with different degrees of geometric asymmetry are the subject of investigation. The qualitative trends of floating potential, plasma potential, electron temperature, and electron density are measured for various phase angles between 0° and 180° in these two reactors to conduct a cross-chamber validation of parameter trends. Similar to the dc self-bias, the plasma parameters show a pronounced dependence on the phase. Their general behavior can be explained by the phase-dependent sheath expansion dynamics as shown by PIC/MCC simulations, where beams of electrons are generated by the respective expanding sheath and accelerated into the plasma bulk, leading to phase-dependent electron temperature and density. However, the measured profiles of the plasma parameters as a function of phase in both experimental setups are not symmetric around θ =90^{° } , unlike the dc self-bias. This observation is confirmed by PIC/MCC simulations, which reveal asymmetrical electron excitation/ionization dynamics at the corresponding phases. This implies that the observed trends are a property of the 2f discharge in combination with a geometrically asymmetric reactor.